(untitled) (Boca Raton, 2001)
Recently there has been a growing awareness of the need to conduct sound and inclusive interdisciplinary research in key academic and applied areas. Interdisciplinary Food Safety Research answers the increasing calls to better understand and analyze the impact of food safety efforts. By collecting a wide range of multidisciplinary examples, the text identifies important areas of research while providing a resource for future group-building activities.
Keywords: Food adulteration and inspection,Giả mạo thực phẩm và kiểm tra